The relevance of daylight for humans - Wirz-Justice, Anna; Skene, Debra J.; Münch, Mirjam (Biochemical pharmacology, 2021)
[Display omitted] Daylight is ubiquitous and is crucial for mammalian vision as well as for non-visual input to the brain via the intrinsically photosensitive retinal ganglion cells (ipRGCs) that express the photopigment melanopsin. The ipRGCs project to the circadian clock in the suprachiasmatic nuclei and thereby ensure entrainment to the 24-hour day-night cycle, and changes in daylength trigger the appropriate seasonal behaviours. The ipRGCs also project to the perihabenular nucleus and surrounding brain regions that modulate mood, stress and learning in animals and humans. Given that light has strong direct effects on mood, cognition, alertness, performance, and sleep, light can be considered a “drug” to treat many clinical conditions. Light therapy is already well established for winter and other depressions and circadian sleep disorders. Beyond visual and non-visual effects via the retina, daylight contributes to prevent myopia in the young by its impact on eye development, and is important for Vitamin D synthesis and bone health via the skin. The sun is the most powerful light source and, dependent on dose, its ultraviolet radiance is toxic for living organisms and can be used as a disinfectant. Most research involves laboratory-based electric light, without the dynamic and spectral changes that daylight undergoes moment by moment. There is a gap between the importance of daylight for human beings and the amount of research being done on this subject. Daylight is taken for granted as an environmental factor, to be enjoyed or avoided, according to conditions. More daylight awareness in architecture and urban design beyond aesthetic values and visual comfort may lead to higher quality work and living environments. Although we do not yet have a factual basis for the assumption that natural daylight is overall “better” than electric light, the environmental debate mandates serious consideration of sunlight not just for solar power but also as biologically necessary for sustainable and healthy living.